(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Laparoscopy has now become the gold standard method for management of a wide range of gynecological ailments including adnexal masses. Laparoscopic surgery has been associated with shorter operating time, shorter duration of hospital-stay, early recovery and significant patient satisfaction. Using most modern image system like 3D-4K & advanced bipolar system like Ligasure, handling difficult procedure becomes easier & operating time becomes further shorter. The present study is conducted to evaluate the effectiveness & safety of laparoscopy in the management of adnexal masses & to find out the superiority of 3D-4K image technology over 2D-4K regarding operating time & handling difficult procedures. Method: The study period was of 36 months, from January 2017to December2019 in a laparoscopy surgery based private hospital, Cumilla, Bangladesh. During this period, 42 patients underwent laparoscopy for various benign adnexal masses. Cases were critically analyzed & Results are presented. Results: Most of the patients were from the age group of 20 to 30 years. Most common indication was serous cyst adenoma (48%). Most common surgical procedure performed was ovarian cystectomy (43%). Average operating time was less in 3D-4K image technology than 2D-4K. Conversion rate was nil in this study. No major complication observed. Minor port site infection found only in 2 cases. Conclusion: Laparoscopic surgery reduces hospital stay, there is less adverse effect, early recovery and better quality of life on surgical treatment of benign adnexal masses. J Bangladesh Coll Phys Surg 2022; 40: 111-115